Factors Influencing Brain Drain Among Health Workers in Ghana - Adjei-Mensah, Sussana (European Journal of Human Resource, 2023)
Purpose: The advent of the covid-19 pandemic exacerbated the need for more professional health workers to serve as front-line workers in hospitals in Ghana and other developing countries. This study aimed to ascertain the factors influencing health workers' brain drain in Ghana. Methodology: The study was a survey with an accessible population of 15510 people in different categories of health workers. Sampling was through stratification for a sample size of 400 respondents across the Greater Accra Region of Ghana. Structured questionnaires were used for the data collection and analyzed using the Statistical Package for Social Sciences (SPSS) as a statistical tool to generate descriptive statistics that included the mean, standard deviation and ranks based on which inferences were drawn. Findings: The study found that government inaction on the conditions of service of health workers such as low remuneration, inadequate opportunities for staff development, poor equipment replacement policies, political interferences in their workplaces, high standards of living and inadequate housing and personal reasons amount to the reasons why Ghana is losing the majority of her finest health workers to the developed nations. The study concluded that the migration of healthcare professionals from developing to developed nations has negative effects on the delivery of healthcare in Ghana especially coming out of a deadly pandemic. Recommendation: The study recommends that government deals with the motivation and hygiene factors as well as the push and pull economic factors that drive many health workers to seek "greener pastures" outside the country hence the trend could continue in the coming years.